Learning principles of accounting in ICT -supported learning environments of Malaysian secondary schools: future-oriented approach - Tan, Boon See; Wong, Su Luan (SpringerOpen, 2020)
This research was undertaken to identify the learning approaches used by Malaysian secondary school students of Principles of Accounting in the context of ICT-supported learning environments. The revised Two-Factor version of the Learning Process Questionnaire (R-LPQ-2F) was adapted to appraise the learning approaches used, while the Technology-Rich Outcomes-Focused Learning Environment Inventory (TROFLEI) was adapted to obtain the perceptions of students in ICT-supported learning environments which practising the ICT-pedagogy. The sample for the study comprised 371 Form Four Malaysian students. There were indications from this study that students employed the deep approach to learning Principles of Accounting; whereas the surface approach was not discernible. Only two scales measured the sub constructs of surface motive and surface strategy, namely aim for qualification and minimising scope of study merged and evolved into what is referred to as the future-oriented approach in this study. Aiming for qualification as a motive is complemented by a non-surface learning strategy of non-minimisation of scope of study, i.e. learning beyond the minimum scope. The future-oriented approach was influenced by socio-cultural and educational contextual factors in Malaysia. The findings also reflected the influence of ICT-supported learning environment perceptions on learning approaches.